Analysis of Mortality from Carcinomas Primary Localized in Region of Lip, Oral Cavity and Pharynx in Central Serbia, 1999-2015 - Milos M. STEPOVIC; Dalibor STAJIC; Marija SEKULIC; Zlata RAJKOVIC; Nela DJONOVIC (Tehran University of Medical Sciences, 2020)
Background: Lip, oral cavity, and pharyngeal cancers have been globally estimated to account for about 3.8% of all cancer cases and 3.6% of cancer deaths. Mortality of these cancers is generally higher in developing than in developed countries. Overall cancer mortality rate in Serbia is one of the highest in the world. The aim of this study was to determine the mortality rate trends and the most common localization of lip, oral and pharyngeal cancers in Serbia. Methods: The study was conducted in 2018 as descriptive epidemiological study and included years from 1999 to 2015. The differences in standardized mortality rates and number of deaths were analyzed with regard to age, gender, and tumor localization. Linear trend and regression were used to determine mortality rate trend. Results: There was statistically significant difference in the number of deaths between men and women in the ages of 40 and over (P < 0.01); male/female cancer mortality ratio was 4.56:1. Generally, the most common localization of this carcinoma was hypopharynx. There was no statistically significant increase of mortality rates from these cancers for both genders (males: y = 4.77 + 0.42x, P = 0.069 % change = +20.35; females: y = 1.03 + 0.01x, P = 0.40 % change = +4) during 17-year period. Conclusion: Promotion of healthy habits, life-styles and regular inspection of mouth by patients and health professionals should be better prioritized especially in developing countries where implementing and improving national health prevention programs are essential.